2019
DOI: 10.22438/jeb/40/2/mrn-830
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a shipwreck as an artificial fish habitat along Goa, west coast of India

Abstract: The objective of the study was to test the hypothesis that submerged shipwrecks along the western coast of India can function as artificial fish habitats with trophic structure of fish assemblages similar to natural rocky reef habitats.The fish assemblages on shipwreck and natural reefs were analysed from September 2013 to December 2016 using diver assisted underwater visual census (UVC). Data collected on fish assemblages were used to compare the fish trophic structure between shipwreck and natural reefs usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The war wrecks are a great challenge to work with, because of their random depths and distances from the coast (Sinopoli et al ., 2015). There are limited fish community studies on such accidental wrecks, in which ROVs (Consoli et al ., 2014; Sinopoli et al ., 2015) and visual census methods were used (Simon et al ., 2013; Sreekanth et al ., 2019). In the Mediterranean Sea, while the fish community studies were mostly conducted with artificial reefs (ARs) such as concrete blocks, pipes and fuel-gas platforms (Charbonnel et al ., 2002; Fabi et al ., 2002; 2004; Lök et al ., 2008; Andaloro et al ., 2011; Gül et al ., 2011; Scarcella et al ., 2011; Consoli et al ., 2013), there was little interest in the artificial wrecks reefs (AWRs) (Simon et al ., 2013; Acarlı et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The war wrecks are a great challenge to work with, because of their random depths and distances from the coast (Sinopoli et al ., 2015). There are limited fish community studies on such accidental wrecks, in which ROVs (Consoli et al ., 2014; Sinopoli et al ., 2015) and visual census methods were used (Simon et al ., 2013; Sreekanth et al ., 2019). In the Mediterranean Sea, while the fish community studies were mostly conducted with artificial reefs (ARs) such as concrete blocks, pipes and fuel-gas platforms (Charbonnel et al ., 2002; Fabi et al ., 2002; 2004; Lök et al ., 2008; Andaloro et al ., 2011; Gül et al ., 2011; Scarcella et al ., 2011; Consoli et al ., 2013), there was little interest in the artificial wrecks reefs (AWRs) (Simon et al ., 2013; Acarlı et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the former studies indicated that fish abundance and/or biomass values at ARs are higher than at natural rocky reefs (NRs) and soft sandy bottoms (SBs) (Honório et al ., 2010; Fagundes-Netto et al ., 2011; Coelho et al ., 2012; Simon et al ., 2013; Consoli et al ., 2014; Ross et al ., 2015; Sreekanth et al ., 2019). Scientists have found that fish communities had differences at a regional and local scale affected by currents (Fulton & Bellwood, 2004), depth (Malcolm et al ., 2011), habitat type (Anderson & Millar, 2004), bottom structure (Grober Dunsmore et al ., 2008; Schultz et al ., 2012) and topographic complexities (Walker et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%